Abatacept inhibits inflammation and onset of rheumatoid arthritis in individuals at high risk (ARIAA): a randomised, international, multicentre, double-blind, placebo-controlled trial - Rech, Jürgen; Tascilar, Koray; Hagen, Melanie; Kleyer, Arnd; Manger, Bernhard; Schönau, Verena; Hueber, Axel; Kleinert, Stefan; Baraliakos, Xenofon; Braun, Jürgen; Kiltz, Uta; Fleck, Martin; et al. (Lancet, 2024)
Background: Individuals with anti-citrullinated protein antibodies (ACPAs) and subclinical inflammatory changes in joints are at high risk of developing rheumatoid arthritis. Treatment strategies to intercept this pre-stage clinical disease remain to be developed. We aimed to assess whether 6-month treatment with abatacept improves inflammation in preclinical rheumatoid arthritis. Methods: The abatacept reversing subclinical inflammation as measured by MRI in ACPA positive arthralgia (ARIAA) study is a randomised, international, multicentre, double-blind, placebo-controlled trial done in 14 hospitals and community centres across Europe (11 in Germany, two in Spain, and one in the Czech Republic). Adults (aged ≥18 years) with ACPA positivity, joint pain (but no swelling), and signs of osteitis, synovitis, or tenosynovitis in hand MRI were randomly assigned (1:1) to weekly subcutaneous abatacept 125 mg or placebo for 6 months followed by a double-blind, drug-free, observation phase for 12 months. The primary outcome was the proportion of participants with any reduction in inflammatory MRI lesions at 6 months. The primary efficacy analysis was done in the modified intention-to-treat population, which included participants who were randomly assigned and received study medication. Safety analyses were conducted in participants who received the study medication and had at least one post-baseline observation. The study was registered with the EUDRA-CT (2014–000555–93). Findings: Between Nov 6, 2014, and June 15, 2021, 139 participants were screened. Of 100 participants, 50 were randomly assigned to abatacept 125 mg and 50 to placebo. Two participants (one from each group) were excluded due to administration failure or refusing treatment; thus, 98 were included in the modified intention-to-treat population. 70 (71%) of 98 participants were female and 28 (29%) of 98 were male. At 6 months, 28 (57%) of 49 participants in the abatacept group and 15 (31%) of 49 participants in the placebo group showed improvement in MRI subclinical inflammation (absolute difference 26·5%, 95% CI 5·9–45·6; p=0·014). Four (8%) of 49 participants in the abatacept group and 17 (35%) of 49 participants in the placebo group developed rheumatoid arthritis (hazard ratio [HR] 0·14 [0·04–0·47]; p=0·0016). Improvement of MRI inflammation (25 [51%] of 49 participants in the abatacept group, 12 [24%] of 49 in the placebo group; p=0·012) and progression to rheumatoid arthritis (17 [35%] of 49, 28 [57%] of 49; HR 0·14 [0·04–0·47]; p=0·018) remained significantly different between the two groups after 18 months, 12 months after the end of the intervention. There were 12 serious adverse events in 11 participants (four [8%] of 48 in the abatacept group and 7 [14%] of 49 in the placebo group). No deaths occurred during the study. Interpretation: 6-month treatment with abatacept decreases MRI inflammation, clinical symptoms, and risk of rheumatoid arthritis development in participants at high risk. The effects of the intervention persist through a 1-year drug-free observation phase. Funding: Innovative Medicine Initiative.
CRIS-Team Scopus Importer:2024-02-23